Exergy and thermo-economic analysis of ghee production plant in dairy industry. (15th January 2019) - Singh, Gurjeet; Singh, P.J.; Tyagi, V.V.; Barnwal, P.; Pandey, A.K.
Abstract: The India's annual milk and ghee production are approximately estimated as 160 MT and 1.72 MT respectively. India has the largest production of Ghee in the dairy Industry worldwide. Ghee consumption in India is 28% annually after fluid milk i.e. 44% due to high consumer demand. The butter churner, butter melter, ghee boiler and ghee clarifier are the key subunits of ghee production plant. The dairy industry is characterised by high energy consumption for production of Ghee and Butter in the country. The thermo-economic analysis and thermodynamic derivatives calculated in this study. The value of the universal exergy efficiency and specific exergy destruction of the plant was found as 34.21% and 438.61 kJ/kg respectively. The cost rate of exergy destruction for the entire plant was calculated as 3270.68 R/H; 39% of which was contributed by boiler for ghee production (ghee boiler). The highest value of percentage relative cost difference was associated with butter melter (97.29%) followed by butter churner (96.73%). The thermo-economic factor butter churner (8.00%) and ghee boiler (1.09%) revealed that impact of capital investment was more influential in former while exergetic degradation appeared to be more noticeable in latter. Highlights: Exergy Efficiency of the plant was performed in this work. Thermo-economic analysis of ghee production plant studied on actual plant data. The Specific Exergy Destruction of plant ascertained to be 438.61 kJ/kg. The Specific Exergy Improvement Potential of plant estimated as 314.26 kJ/kg. Total plant operating cost and specific manufacturing cost of Ghee is calculated.